THE VALUATION OF INTANGIBLES (Book). - Yang, J. M. (The Accounting Review, 1927)
Abstract The article focuses on the valuation of intangibles in business practices for the purpose of purchase and sale. There have been a large number of variable factors that have to be taken into account in the process. However, there are several general considerations which are to a greater or less extent taken into account in all case of valuation of intangibles. In buying a business with an established earning power in excess of what is considered ordinary in the particular line of industry, the purchaser expects to pay for the capitalized value of the estimated excess earnings which may be judged to continue for a fairly definite number of years. In computing this value, a number of factors have to be considered, like, the earnings of the concern; the value of investment or which a normal rate of income is to be allowed; normal rate of earnings for the industry concerned; the amount of the excess earnings that can be transferred; the number of years during which the transferable excess earnings may be expected to accrue; and the rate for capitalizing the excess earnings thus determined.